Leaf micronutrients in guava fertigated with biofertilizer and nitrogen in semiarid - Santana, Elisson Alves; Lobo, Jackson Teixeira; Pereira, Renan Nunes; Lima, Augusto Miguel Nascimento; Cunha, Jaílson Cavalcante; Cavalcante, Ítalo Herbert Lucena (Comunicata Scientiae, 2017)
Required in small amounts, micronutrients play a key role for adequate plant development, which can be supplied by synthetic or organic fertilizers, such as biofertilizers. Thus, an experiment was conducted between July 2014 and August 2015, in the experimental area of the Federal University of the São Francisco Valley, Petrolina-PE, Brazil, to evaluate the micronutrient leaf concentrations of Paluma guava as a function of fertigation with bovine biofertilizer and Nitrogen fertilization. The experimental design was a randomized complete block design (5 x 2) referring to the concentrations of bovine biofertilizer (0, 2.5, 5.0, 7.5 and 10%) and N-fertilizing (50% and 100% of N dose following plant demand), with four replicates and five plants per plot. Only the leaf Mn concentrations are affected by bovine biofertilizer in guava trees fertigated with 100% of recommended N. Leaf concentrations of all the micronutrients (Mn, B, Fe and Zn) are not influenced by nitrogen fertigation. The biofertilizer is efficient in providing Fe.